Firm size and value - БогатыревКонстантин Викторович; ДондоковБулат Зориктуевич; ЖеребцоваМалика Камильевна; ПавловИван Игоревич; ТихоновАлександр Александрович (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2013)
Konstantin V. Bogatyrev - Moscow State University. M.V. Lomonosov Moscow State University. E-mail: konstantin.bogatyrev@yahoo.com Bulat Zoriktuevich Dondokov Malika Kamylevna Zherebtsova Ivan Igorevich Pavlov Alexander Alexandrovich Tikhonov This paper presents an overview of the research on the size effect in equity returns. This paper provides an overview of the academic debate on the causes of the size effect. Based on various studies, possible explanations for the size effect are summarized. The paper suggests possible directions for further research and methodological improvements, including those for the Russian stock market.